AGRICULTURE POLICY REFORMS IN BH AND WESTERN BALKANS IN RELATION TO THE EU - Rokvić, Gordana (Economics of Agriculture, 2011)
Western Balkan countries are undergoing trough the reform process of agriculture and rural development sector in line with EU policies and legislation. On the other hand the EU is going through the reform process towards designing new Common Agricultural Policy for the period 2007-2013 years. This paper aims to link these reforms through a comparative analysis of general indicators of agricultural development of EU and Western Balkan countries, and through analysis of the main objectives and measures of support that are being identifed in the CAP and IPARD regulations, the two main regulations for support of countries to implement agricultural policies and reforms.